Development of an RT-LAMP assay for detecting tet(M) in Enterococcus species: enhancing AMR surveillance within the One Health sectors. - Mussa, Ebthag A.M.; Al-Maleki, Anis Rageh; Aljaberi, Musheer A.; Alsalahi, Abdulsamad; Mohd Desa, Mohd Nasir; Jasni, Azmiza Syawani; Ramanoon, Siti Zubaidah; M. Abdallah, Atiyeh; Hamat, Rukman Awang (Multidisciplinary Digital Publishing Institute, 2025)
The increasing prevalence of antimicrobial-resistant (AMR) bacteria in humans, animals, and the environment underscores the necessity for a rapid, sensitive, and specific method to identify resistance genes. Objectives: This study aims to develop a reliable detection tool for identifying the tetracycline-resistant gene tet(M) in Enterococcus species using a real-time loop-mediated isothermal amplification (RT-LAMP) assay. Real-time visualization through a turbidimeter enabled precise estimation of time-to-positivity for gene detection. Methodology: Six primers were designed using PrimerExplorer v.5, and the assay was optimized across different temperatures and incubation times. Validation was conducted by testing 52 tet(M)-positive clinical enterococci isolates and spiking urine samples from a healthy volunteer and a cow with tet(M)-positive Enterococcus species. Results: The tet(M) gene was detected as early as 33 min, with optimal amplification occurring within 60 min at 60 °C. The assay demonstrated 100% specificity with the established primers. The sigmoidal graphs were corroborated with visual confirmation methods, including a green color change (visible to the naked eye), green fluorescence (under UV light), and a 200 bp PCR product observed via agarose gel electrophoresis. Notably, the tet(M) RT-LAMP assay exhibited a detection limit of 0.001 pg/μL, significantly surpassing conventional PCR, which had a detection limit of 0.1 pg/μL. Conclusions: This rapid, cost-effective, highly sensitive, and specific tet(M) RT-LAMP assay holds significant promise as a surveillance tool for antimicrobial resistance monitoring within a One Health framework, particularly in low-resource countries.